2014
DOI: 10.1097/bpo.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Is There Still a Place for Cast Wedging in Pediatric Forearm Fractures?

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 44 publications
(70 reference statements)
2
25
0
Order By: Relevance
“…Overall, three studies meeting the inclusion criteria mentioned above were identified during the systematic literature search. 16 - 18 Table 1 gives an overview of the studies’ characteristics. In total, 316 patients were included (Keenan and Clegg: 17 six patients, Samora et al: 18 61 patients, Kattan et al: 16 249 patients).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, three studies meeting the inclusion criteria mentioned above were identified during the systematic literature search. 16 - 18 Table 1 gives an overview of the studies’ characteristics. In total, 316 patients were included (Keenan and Clegg: 17 six patients, Samora et al: 18 61 patients, Kattan et al: 16 249 patients).…”
Section: Resultsmentioning
confidence: 99%
“… 16 - 18 Table 1 gives an overview of the studies’ characteristics. In total, 316 patients were included (Keenan and Clegg: 17 six patients, Samora et al: 18 61 patients, Kattan et al: 16 249 patients). The study design was prospective in the study by Samora et al, 18 retrospective in the study by Kattan et al 16 and Keenan and Clegg 17 did not provide the study design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations